If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x)(3x + 12) = 180 Remove parenthesis around (9x) 9x(3x + 12) = 180 Reorder the terms: 9x(12 + 3x) = 180 (12 * 9x + 3x * 9x) = 180 (108x + 27x2) = 180 Solving 108x + 27x2 = 180 Solving for variable 'x'. Reorder the terms: -180 + 108x + 27x2 = 180 + -180 Combine like terms: 180 + -180 = 0 -180 + 108x + 27x2 = 0 Factor out the Greatest Common Factor (GCF), '9'. 9(-20 + 12x + 3x2) = 0 Ignore the factor 9.Subproblem 1
Set the factor '(-20 + 12x + 3x2)' equal to zero and attempt to solve: Simplifying -20 + 12x + 3x2 = 0 Solving -20 + 12x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -6.666666667 + 4x + x2 = 0 Move the constant term to the right: Add '6.666666667' to each side of the equation. -6.666666667 + 4x + 6.666666667 + x2 = 0 + 6.666666667 Reorder the terms: -6.666666667 + 6.666666667 + 4x + x2 = 0 + 6.666666667 Combine like terms: -6.666666667 + 6.666666667 = 0.000000000 0.000000000 + 4x + x2 = 0 + 6.666666667 4x + x2 = 0 + 6.666666667 Combine like terms: 0 + 6.666666667 = 6.666666667 4x + x2 = 6.666666667 The x term is 4x. Take half its coefficient (2). Square it (4) and add it to both sides. Add '4' to each side of the equation. 4x + 4 + x2 = 6.666666667 + 4 Reorder the terms: 4 + 4x + x2 = 6.666666667 + 4 Combine like terms: 6.666666667 + 4 = 10.666666667 4 + 4x + x2 = 10.666666667 Factor a perfect square on the left side: (x + 2)(x + 2) = 10.666666667 Calculate the square root of the right side: 3.265986324 Break this problem into two subproblems by setting (x + 2) equal to 3.265986324 and -3.265986324.Subproblem 1
x + 2 = 3.265986324 Simplifying x + 2 = 3.265986324 Reorder the terms: 2 + x = 3.265986324 Solving 2 + x = 3.265986324 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 3.265986324 + -2 Combine like terms: 2 + -2 = 0 0 + x = 3.265986324 + -2 x = 3.265986324 + -2 Combine like terms: 3.265986324 + -2 = 1.265986324 x = 1.265986324 Simplifying x = 1.265986324Subproblem 2
x + 2 = -3.265986324 Simplifying x + 2 = -3.265986324 Reorder the terms: 2 + x = -3.265986324 Solving 2 + x = -3.265986324 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = -3.265986324 + -2 Combine like terms: 2 + -2 = 0 0 + x = -3.265986324 + -2 x = -3.265986324 + -2 Combine like terms: -3.265986324 + -2 = -5.265986324 x = -5.265986324 Simplifying x = -5.265986324Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.265986324, -5.265986324}Solution
x = {1.265986324, -5.265986324}
| 24=9r-3r | | 15x^4-45x^3=0 | | -7-5x=9x+15 | | 6x+8=120-10x | | 8x=1/5 | | 2t+5+3t-4t=2+3 | | -7x-8y=19 | | -5/9m=-1/4 | | -20=5/13x | | -20x=5/13x | | 10p+6=4p+22 | | 3(2x+9)=-33+12 | | 20x+11/12-19x=5/24 | | -4y-2=-3y-9 | | -43=x | | -(-2a+2)=-6(3+9a) | | t-15=19 | | 25+5-10(y+4)= | | 4a+12=4a+6a | | 2x+5=3x+-1 | | 7(8+3x)=19 | | 8t+3(3t-2)=-5t-10 | | 5-2x/7=9/14 | | 5(3x-6)-3(x+1)-19x= | | 1/8+y=-7/16 | | -96=z+-83 | | 3x-3=21x+9 | | 8x+7=87 | | 4(-4y^5)= | | 3x=2x+17 | | x-1/7=13/14 | | (6x+1)(x-7)=0 |